Effect of Eco-Friendly Product Experience and Green Identity on Intention to Switch - Hirianto, Reno Firman; Adhihendra, Brian Gregory; Candra, Maeda Dicky; Mayasari, Desy; Ayuninggar, Lintang (Jurnal Analisis Bisnis Ekonomi, 2023)
This research focuses on studies related to green marketing and intention to switch. This is based on the current environmental conditions, which are adversely affected by the sustainability of uncontrolled economic activities. The focus of this research will be to study the intention to switch consumers of packaged beverage products which are influenced by Green Product Experience and Green-self Identity. In addition, this research will also fill in the gaps of previous research, where the variables of Green Product Experience and Green-self Identity were studied more in the context of high-involvement products. The method used in this research is a quantitative survey. The data processing uses the SEM-PLS application. The results of this study indicate that in the context of products with low involvement, consumers tend to have the intention to switch even though they already have an understanding and experience related to environmentally friendly products. Keyword: Green Product Experience, Green-self Identity, Intention to Switch